(untitled) (Bangladesh Journal of Medical Microbiology, 2009)
Leptospirosis is a zoonotic disease that has been recognized as an important global health problem because of its increasing incidence in many countries and occurrence of several large outbreaks in recent years. Due to variability of clinical features and limited availability of laboratory facilities in endemic countries, the disease remains largely under-reported. Early and specific diagnosis is important to ensure a favourable outcome. Isolation of Leptospirosis is labourious and time-consuming. Direct demonstration of Leptospira from clinical specimens by dark-field microscopy (DFM), direct immunofluorescence, and immuno-peroxidase staining all lack specificity. Until now serological testing has been most frequently used to confirm diagnosis. Microscopic agglutination test (MAT) is the current gold standard but the technique is not simple and is only done in a few reference laboratories. To overcome these difficulties several test methods have been developed to detect IgM antibodies that are detectable after about 5th day of illness. In this paper, the microbiology, epidemiology and laboratory diagnosis of Leptospirosis have been discussed, and critically reviewed the advantages and disadvantages of various laboratory tests for the diagnosis of the disease. doi: 10.3329/bjmm.v3i1.2970 Bangladesh J Med Microbiol 2009; 03 (01): 39-43